The App Economy : Making Sense of Platform Power in the Age of AI - Konrad Kollnig (Bristol University Press, 2026)
Available open access digitally under CC-BY-NC-ND licence. Mobile apps have transformed how we live, work and connect – but at what cost? This book examines the immense power Apple and Google wield over society, arising from their control of app stores as well as mobile operating systems and browsers. With the EU's new Digital Services Act defining their influence as a potential'systemic risk', Konrad Kollnig unpacks the implications for competition, privacy, and regulation. Offering a clear roadmap for scholars as well as policy makers, this book not only reveals the hidden risks of app ecosystems but also outlines practical solutions for ensuring fairer digital markets.